1997
DOI: 10.1128/jcm.35.6.1344-1347.1997
|View full text |Cite
|
Sign up to set email alerts
|

Equally high prevalences of infection with cagA-positive Helicobacter pylori in Chinese patients with peptic ulcer disease and those with chronic gastritis-associated dyspepsia

Abstract: Helicobacter pylori isolates in the Western world possess the cytotoxin-associated gene A (cagA). cagA-positive H. pylori is found to be associated with peptic ulcer disease (PUD) and gastric adenocarcinoma. To investigate the cagA status of H. pylori isolates from Chinese patients with PUD and chronic gastritis (CG), H. pylori populations from 83 patients, 48 with PUD and 35 with CG, were assessed by two different cagA-specific PCRs, Southern blotting, and colony hybridization. The combined results from PCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
72
2
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 21 publications
7
72
2
3
Order By: Relevance
“…Although this prevalence is higher than that reported previously for the Malaysian population [11,40], this degree of variation between studies in an individual country is not appreciably different from other studies in east Asian populations, such as Korea, Thailand, and Japan [12,[41][42][43][44][45] and may be partially explained by the difference in sequence and number of PCR primers used to detect cagA. The finding that two isolates were PCR negative for the cagA constant region but were positive for the cagA variable region questions the adequacy of utilizing a single primer set for the detection of cagA, especially when strains are isolated from different populations [42,46,47]. The high prevalence of cagA identified in the current study precluded any association between cagA per se and more severe disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Although this prevalence is higher than that reported previously for the Malaysian population [11,40], this degree of variation between studies in an individual country is not appreciably different from other studies in east Asian populations, such as Korea, Thailand, and Japan [12,[41][42][43][44][45] and may be partially explained by the difference in sequence and number of PCR primers used to detect cagA. The finding that two isolates were PCR negative for the cagA constant region but were positive for the cagA variable region questions the adequacy of utilizing a single primer set for the detection of cagA, especially when strains are isolated from different populations [42,46,47]. The high prevalence of cagA identified in the current study precluded any association between cagA per se and more severe disease development.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cagA-positive strains have been observed in European non-ulcer patients previously, but have more active gastritis characterised by increased polymorphonuclear cell in¢ltration into the gastric epithelium [48,50] and a greater likelihood of developing intestinal metaplasia [50]. However, equally high prevalences of cagA-positive isolates from PUD and NUD patients have been reported also in Chinese patients [51] and this trait is considered not a useful marker of enhanced virulence in the Chinese and Japanese populations [51^53]. Of the isolates from Irish duodenal ulcer patients, 80% were cagA-positive, which is comparable to those of about 80^100% that have been reported for di¡erent populations worldwide [42,43,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…interleukin (IL)-8, IL-6 and tumour necrosis factor (TNF)-a (14). It has been reported that cagA gene is present in 70-90% of clinical isolates of H. pylori and almost all of whom express CagA protein (10,13,15,16).…”
Section: Introductionmentioning
confidence: 99%